(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The objective of the research was to study the possible competition between roots of apple-trees and grass under the influence of applied moisture regulation methods. No analogical research has been performed in Latvia so far. The investigation was done on the base of an existing trial planted in 1997 with cultivar `Melba` at 1.5 × 4 m planting distances. Three different treatments of soil moisture management were compared: control, sawdust mulch and fertigation. Inter-row strips were covered by grass vegetation (Lolium perenne and Poa pratensis, in proportion 1:3). The horizontal and vertical spacing of the main root mass was determined, as well as the distance and depth of the spread of grass roots from the inter- row strip into the tree strip. The results of the research show that mulching and fertigation have significant influence on the horizontal and vertical root spacing of grass grown in the inter-row strip, which can be an evidence of competition between apple-trees and grass for water and nutrients.